172k views
1 vote
How would you find the 27th term Given the arithmetic sequence: -1, -3, -5, -7, . . .

User Bassxzero
by
5.7k points

2 Answers

2 votes
yerrrrrrrrrrrrrrrr he/she is gonna answer it for u
User Carlos Garces
by
5.5k points
5 votes

Answer: - 53

Explanation:

For a sequence to be arithmetic sequence then there must be a common difference (d). Common difference is given by :

d =
t_(2) -
t_(1) =
t_(3) -
t_(2) ...

From the sequence given :

a = -1

d = -3 - (-1 )

d = -3 + 1

d = -2

The formula for nth term of an arithmetic sequence is given as :


t_(n) = a + ( n - 1 ) d

where n is the number of terms , therefore, the 27th term will be


t_(27) = a + (27 - 1 ) d

substituting the value of a and d , we have


t_(27) = - 1 + (26) x -2


t_(27) = -1 -52


t_(27) = -53

Therefore , the 27th term = - 53

User Supreeth Meka
by
5.7k points